Approaches of Slovak Industrial Companies to Development of Business Strategy - Laššák, Vladimir; Ďad'o, Jaroslav (Approaches of Slovak Industrial Companies to Development of Business Strategy, 2006)
Competitiveness of business organisations domestic in Slovak republic is influenced by various factors. The most important are continuous integration into political and economic structures of European Union and globalisation of the world economy. Paper describes finding from the research concerning ability of Slovak industrial companies to compete on domestic and world market. We studied how companies prepared their last business strategies. We described positive and negative impact of globalisation on business in Slovakia and identified expected changes in period of next five years. We have described typical measures that companies realed as a reaction to globalisation pressures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 392-401